Virtual Active Learning to Maximize Knowledge Acquisition in Nursing Students: A Comparative Study - Guillermo Moreno; Alfonso Meneses-Monroy; Samir Mohamedi-Abdelkader; Felice Curcio; Raquel Domínguez-Capilla; Carmen Martínez-Rincón; Enrique Pacheco Del Cerro; L. Iván Mayor-Silva (MDPI AG, 2024)
Background: Nursing students need to acquire knowledge through active methods that promote critical thinking and decision making. The purpose of this study is to analyze whether there are differences in the acquisition of knowledge by nursing students between active face-to-face or virtual teaching methods. Methods: In this comparative study, nursing students enrolled in the psychology course were divided into two groups: a face-to-face group that received active teaching methods and a virtual group. The virtual group was exposed to the Effective Learning Strategy (ELS), which included seminars based on video content through the Virtual Campus and answering questions using the H5P tool. In addition, participants engaged in reflection tasks on the content. Covariate data were collected, and knowledge tests were administered to both groups before and after the course. After three months, subjects were re-evaluated with a final exam to assess content retention. Results: A total of 280 students were randomized. No differences were found in students' scores at the end of the knowledge test or in their final grades in the subject. Having study habits (b = 0.12, p = 0.03) and social support from relevant people (b = 0.09; p = 0.03) were associated with better post-intervention scores, and inversely with social support from friends (b = −0.12, p < 0.01). Final grades were inversely associated with digital safety literacy (b = −0.101, p = 0.01). No factors were associated with the scores of each group separately. Conclusions: The ELS virtual active learning model is as effective as face-to-face active learning methods for teaching psychology to first-year nursing students. This study was not registered.